Peran Guru dalam Identitas Sosial Siswa di Era Teknologi (Studi Kasus di MIN 1 Kutai Timur) - Eka Wahyuni; Muhammad Azka Wahyu Aroby; Muhammad Yasin (PT. Pustaka Andil Lestari, 2024)
This research aims to shape students' social identities experiencing significant transformation, especially regarding the use of technology. Using a qualitative approach with case studies as the main method, data was collected through participant observation, interviews with teachers and students, as well as content analysis of digital platforms used in the learning process. The results show that teachers have a significant role in guiding students on the healthy and responsible use of technology, creating an inclusive and supportive learning environment where students feel safe to share thoughts and ideas. This holistic approach also helps students develop a strong and balanced social identity, which is an important aspect in facing the increasingly complex challenges of the modern world. The practical implications of this research are the importance of teacher training in the use of technology for positive educational purposes, as well as the need for support from all stakeholders to create an educational ecosystem that supports students' holistic development in the digital era.